Neighborville, Norton County - Milnes, Jennifer L. (Kansas State University, The Chapman Center for Rural Studies, 2013)
Jennifer Milnes chose to write about this town to show that a town can persist as long as the people stay connected. The history is still among us, we just have to dig a little deeper sometimes. By talking and networking in surrounding communities, she was able to find out more about this persistent town than she thought was possible. Her study includes maps, personal photographs, and information collected through informal interviews.
Jennifer L Milnes, “Neighborville, Norton County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/125.
Keywords: Bieber; Calvert; Emmett Township; Neighborville; Norton County; US Highway 36